Fatores de desempenho gerencial de administradores de centros/sistemas de informação: subsídios ao processo de capacitação gerencial - Ana Lucia Neves Pimenta (1993)
This exploratorydescriptive survey emphasizes the contents of managerial work. It specifically investigates, as a main issue, which are the performance factors of managers in information centers and systems, that is, requirements for a manager effective performance in his organizational role. They include, as whole, requirements in terms of knowledge needed for the understanding of managerial work, skills directly related to the performance, and attitudes appropriate to the organizational role. This study was based upon two main procedures: the first was as search, through specialized literature, for authors concept of managerial performance; and the second, a survey on the very managers concepts, as heads of information centers and systems, about own performance. Concerning managerial performance, the following aspects were analysed: relevance attributed to managerial roles and managers ability to perform them; requirements in terms of needed knowledge, skills and attitudes; and barriers and challenges to performance. The study considered the mangers academic background (be they librarians or not), as well as the kind of organization at which they work (public, private and mixed enterprises). Concerning managerial performance, the study revealed that there is a positive correlation between relevance attributed to roles and the managers ability to perform them. Performance factors are perceived to be related to the following aspects: knowledge about the organizational internal environment, skills concerning the capacity of receiving, processing, transmitting and utilizing information, and attitudes that allow and propitiate changes in information centers and systems. Performance factors, barriers and challenges, identified by theis study in relation to managerial performance, are practically the same for both kinds of managers and for all types of organization at which they work.